Predicting molecular crystals of polynitrogen (N6) structures with cage-like geometries using ab initio evolutionary algorithm - D. Freitas, W.; C. Mazzoni, M.S.; S. Matos, M.J.; R. L. Galvão, B. (Chemical physics letters, 2024)
In this work, we employed Density Functional Theory calculations combined with search techniques based on evolutionary algorithms to predict and characterize crystalline structures composed of nitrogen (N6) cage-like molecules. We found stable molecular crystals and a rich phenomenology associated with their behavior under pressure, including atomic rebonding and semiconductor-metal transitions. This investigation resides in the context of high-energy-density materials, since molecular species containing only nitrogen atoms tend to dissociate into N2 molecules, releasing large amounts of energy. [Display omitted] •Nitrogen allotropes have potential as clean high energy-density materials.•Prediction of crystal structures is performed using evolutionary algorithms.•New N6molecular crystals were obtained and analyzed by computational techniques.•We predict stable structures which can undergo a semiconductor-metal transition.